Perilaku Seksual Sebagai Risiko Seropositif Imunoglobulin G (IgG) Toxoplasma Gondii Pada Pria Homoseksual Penderita HIV - Nur Rizky Ramadhani; Rizky Fajar Meirawan (Jurnal Health Sains, 2023)
Sexual behavior is one of the factors thought to be associated with Toxoplasma gondii infection. Several studies have shown that sexual behavior such as oral sex, a history of injuries to the genital organs during sexual intercourse, and working as a sex worker are associated with Toxoplasma gondii infection. In addition, a history of injecting narcotic use is also associated with Toxoplasma gondii infection. One method to determine infection status is serological examination, through measurement of immunoglobulin G (IgG). IgG seropositivity is the basis for determining the status of Toxoplasma gondii infection in the chronic or latent phase. This study aims to determine the relationship between sexual behavior and history of injecting drug use with Toxoplasma gondii infection based on IgG serological status. The study population in this study were 56 homosexual men with Human Immunodeficiency Virus (HIV) in the DKI Jakarta area, Bogor Regency and City, and Depok City. In this study, the infection status of Toxoplasma gondii was measured by the ELISA method at the Department of Parasitology, Faculty of Medicine, University of Indonesia. Sexual behavior and history of injecting drug use were measured using a questionnaire. The results of the study proved that 38 samples had positive serological status, 17 samples had negative serological status, and 1 sample was in the borderline range. Based on an analysis using the logistic regression test, age, education, getting paid for having sex, using condoms during oral sex, and a history of injuries to the genital organs during sex are risk factors for Toxoplasma gondii infection.